Academic performance measured by the reading strategies for the english language - Mera Velásquez, Francisco; Gómez Sigcha, Jacqueline María; Cepeda Avila, Katuska (Revista Minerva, 2022)
The main essence of any language is communication. A language is the code that human beings use to interpret the reality that surrounds them; and at the same time transfer those perceptions. Language, thought, and reality form a related and indissoluble trilogy. Based on these approaches to the philosophy of language, academics have designed strategies to enhance the learning process of English as a foreign language that are based on the interests, motivations, and needs of students. Academic instruction is based on printed and multimedia material as a means of communicating updated information, which in the vast majority of cases is in English, which is why this language has taken a leading role as a lingua franca in science and technology. As a result of this, students need to process a significant amount of written and oral information in this language that has become a source of knowledge. College students must understand and be fluent in English to maintain an up-to-date and objective holistic view of the world so that they can make informed decisions during their pre-professional preparation and beyond. When teaching English for specific purposes, this subject meets the needs of students to read and understand written texts in English related to their field of study. Thus, the objectives of an English course must be focused on the needs of the students and aimed at developing the skills of reading, writing, speaking and listening, so that they understand the manuals, brochures, tables, diagrams, graphs, abstracts, specialized journals that are part of an authentic corpus. The learning process directed to specific purposes has evolved according to the different pedagogical currents that have gone from the behaviorist theory to the cognitivist to the constructivist one. However, there is concern about the poor academic performance related to comprehension in university students when it comes to reading texts written in English. This is where the problem that drives this research lies; Although the learning process has individual endogenous characteristics, it also depends on the mediation of the teacher, classmates and the surrounding cultural context, which are proposed in constructivist theory.